Penyelesaian Hukum Akibat Wanprestasi Terhadap Perjanjian Utang Piutang (Studi Putusan Nomor 70/Pdt.G/2024/Pn Sdw) - Prasetia, Ade Nufi; Akmalia, Iftita; Habibie, M. Mirza; Rosidi, M.; Dwi Kusworo , Anjar (Jurnal sosial dan sains, 2025)
This research analyzes the legal settlement due to default in a debt and credit agreement with a focus on Decision Number 70/Pdt.G/2024/PN Sdw. Debt and credit as a fundamental economic activity in society often causes legal problems, especially when debtors fail to fulfill their obligations. The case studied involved a debt and credit agreement worth Rp 100,000,000 with 12% interest per month between Masius Heri as the creditor and Tairudi as the debtor, where the debtor failed to fulfill his obligations despite having provided collateral in the form of Excha invoice documents. This research uses a normative juridical method with a case study approach to examine the legal responsibilities of parties who make defaults and the dispute resolution mechanisms available in the Indonesian legal system. Data was collected through a literature study of relevant laws and regulations, court decisions, and legal literature. The results show that the responsibilities of debtors who default include the obligation to pay principal debt, interest according to the agreement, compensation which includes costs, losses, and moratoir interest, as well as court costs. Dispute resolution mechanisms can be pursued through non-litigation channels (negotiation, mediation, arbitration) or litigation in the District Court. In addition, there is a need for formal collateral binding, good documentation, and utilization of mediation as a more efficient alternative to dispute resolution before filing a lawsuit in court.